Peran Iman Kristen Dalam Mengarahkan Penggunaan Teknologi Modern - Marina Dilon Sipahutar1,; Bernard B. Lubis,; Kronika Pasaribu,; Rani L. Tobing,; April Y.L. Lase,; Deva M. Simanungkalit, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Modern technological advances have had a significant impact on human life. On the one hand, technology facilitates communication, education, healthcare, and productivity. But on the other hand, technology, especially if not used wisely, can bring moral, social, and spiritual issues. This study aims to explore how Christian faith serves to guide the responsible use of modern technology. This study uses a qualitative approach using theological literature, Christian ethics, and technology. This study shows that Christian faith motivates character, self-control, and moral responsibility in digital activities. Christian faith values love, wisdom, and integrity, which serve as a guide in responding to modern technology. Christian faith has and will continue to motivate people to use technology for service, character development, and for the glory of God.